Spinoffs and the Mobility of U.S. Merchant Semiconductor Inventors - Cheyre, Cristobal; Klepper, Steven; Veloso, Francisco (Management Science, 2015)
Data on inventors and assignees of patents are used to analyze the mobility of semiconductor inventors. Exploiting data on the origins of semiconductor producers with larger sales, we argue that the higher mobility of semiconductor inventors in Silicon Valley is in great part due to the entry of spinoffs there. Our empirical evidence suggests that spinoff entry promoted mobility in Silicon Valley even before the industry was clustered there. Agglomeration economies and the ban on noncompete covenants may influence spinoff entry, but spinoffs promote mobility even in the absence of those conditions. Because most of the greater inventor mobility in Silicon Valley corresponds to inventors moving from incumbents to recent entrants, the benefits that arise from greater mobility rates will be disproportionately reaped by new firms. This paper was accepted by Lee Fleming, entrepreneurship and innovation.